2020
DOI: 10.1364/prj.383551
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of mode distortion induced by stimulated Raman scattering in high-power fiber amplifiers

Abstract: The experimental investigation of mode distortion induced by stimulated Raman scattering (SRS) in a high-power fiber amplifier, which includes the evolutions of optical spectra, spatial beam profiles, and time-frequency characteristics, has been carried out in detail. Temporal-frequency characteristics have been studied for the first time, to the best of our knowledge, by using a low-speed camera and high-speed photodiode traces, which revealed that temporal-frequency characteristics of SRS-induced mode distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Yb 3+ ‐doped silica fiber has been an ideal gain medium in high‐energy and high‐power fiber laser applications 1, 2 . The extreme increase in power density in the core leads to a strong nonlinear effect and even damage the fiber end facets in the conventional double‐clad fibers 3, 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yb 3+ ‐doped silica fiber has been an ideal gain medium in high‐energy and high‐power fiber laser applications 1, 2 . The extreme increase in power density in the core leads to a strong nonlinear effect and even damage the fiber end facets in the conventional double‐clad fibers 3, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…
Yb 3+ -doped silica fiber has been an ideal gain medium in high-energy and high-power fiber laser applications. 1,2 The extreme increase in power density in the core leads to a strong nonlinear effect and even damage the fiber end facets in the conventional double-clad fibers. 3,4 To avoid these harmful effects, large-mode-area (LMA) designs have been performed owing to their large core diameter and effective mode area.
…”
mentioning
confidence: 99%
“…It is well known that the SRS effect results in the transfer of the signal power to Stokes light and the broadening of the linewidth asymmetrically [2]. Recently, a new phenomenon, named SRS-induced mode distortion, has also been observed in high power fiber lasers [3][4][5], which renders the single mode beam into a multi-mode operation and deteriorates the spatial brightness severely. The phenomenon was first observed by Hejaz et al [3], and Chu et al [4] studied the corresponding temporal-frequency characteristics, which revealed that SRS-induced mode distortion fluctuates on a time scale of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…The key characteristic of SRS-induced mode distortion was reported as follows: when SRS emerges, the SRS-induced mode distortion appears immediately, and when the SRS effect is suppressed, the SRS-induced mode distortion disappears immediately [31,34] . In addition, the SRS-induced mode distortion could cause time-domain fluctuations in the output power, and the fluctuation frequency is just several hertz [35] .…”
Section: Introductionmentioning
confidence: 99%